Doctor, how can we help you? Qualitative interview study to identify key interventions to target burnout in hospital doctors - Blánaid Hayes; Gillian Walsh; Yseult Freeney; Siobhain McArdle (BMJ Open)
Objective To identify priority interventions for the prevention and reduction of work stress and burnout in hospital doctors through analysis of (1) doctors’ experiences of work stress and burnout and (2) their preferences with respect to interventions.Design Qualitative design using semistructured interviews analysed with deductive thematic analysis.Setting Hospitals in Ireland.Participants 32 hospital doctors (16 practising consultants and 16 doctors in training) from a range of specialties, career stages, hospital types and locations.Results Practical, system-focused interventions were found to be most needed. Challenges with basic entitlements, that is, accessing statutory leave, knowing in advance when leave can be taken and being adequately covered when on leave were identified as requiring urgent attention. Other priority interventions identified were the integration of psychological support in the everyday working environment, time and training for clinical line managers to perform key management activities such as debriefing and education interventions which highlight work stress risks and care pathways, teach self-care and train doctors in how to support one another.Conclusions Hospital doctors are feeling the effects of greater demand and fewer resources. What they most urgently need is adequate staffing levels, access to statutory leave and adequate cover when on leave. Doctors do not receive the support they need from their clinical line managers, who lack the skills and time to excel as people managers. Organisations should focus on developing clinical management skills across the system. The culture of medicine needs to change from stigmatisation and competitiveness to compassion and collaboration. Organisations, medical schools and professional bodies can steer this change through education.